Addressing the nutritional needs of older people in residential care homes - Joy Merrell (Health & Social Care in the Community, 2012)
Background: In the United Kingdom and Europe, malnutrition in older people is a significant problem as it predisposes to disease, impedes recovery from illness, increases mortality and is costly to society. Despite the high number of older people potentially at risk, malnutrition in care homes has been under explored. There is concern that national guidelines regarding the nutritional care of older people in residential care homes are not always implemented. Aim: This qualitative study informed by ethnography explored the factors which influence the nutritional care provided to residents in two different types of Local Authority residential care homes (providing personal care) in Wales. One home had communal dining rooms, the other had eight bedded units with their own kitchen and dining facilities. Methods: The total sample was 45 participants, comprised of 19 staff (managers, care workers and catering staff), 16 residents and 10 residents’ relatives. Mixed methods were employed including observation, individual qualitative interviews, focus groups and documentary review. The ways in which staff assessed and addressed residents’ nutritional needs is the focus of this paper.Findings and Conclusion: In both care homes, staff strove to be responsive to residents’ dietary preferences, provided person centred care and worked in partnership with residents and their families to provide nutritious food in a homely environment. However, nutritional screening to identify those at risk of malnutrition was not conducted in either home, contrary to national guidelines, but reliance was placed on ad hoc observation and monitoring. A need for further training for care home staff regarding the importance of nutrition in maintaining health in older people, use of nutritional screening and special dietary needs was identified. Shared nutrition training between health and social care staff needs to be furthered and policy implications in terms of an enhanced regulatory focus on maintaining nutritional needs in care homes are recommended